Linking mycorrhizal fungi and soil nutrients to vegetative and reproductive ruderal plant development in a fragmented forest at central Argentina - Grilli, Gabriel (2013)
We studied the actual links between mycorrhizal fungi, nutrient availability and plant development in several sites of fragmented Chaco forests. Specifically, we evaluated whether arbuscular mycorrhizal fungi (AMF) and dark septate endophytes (DSE) colonization and availability of soil nutrients are related to growth (biomass and plant height) and reproductive traits (pollen size and pollen and fruit production) of two ruderal, annual, congeneric Euphorbia species along a gradient of forest fragmentation. We assessed relationships between forest fragment size and isolation, nutrient availability, mycorrhizal fungal variables and plant development at eleven Chaquean forest fragments (0.5?1000 ha) immersed in an agricultural landscape in central Argentina. Mycorrhizal colonization was not related to forest fragment isolation, positively related to forest fragment size and negatively related to soil nutrient availability in both hosts along the fragmentation gradient. Plant reproductive and vegetative traits were related to mycorrhizal colonization. In general, plant height, biomass, and fruit production were negatively related to AMF, and pollen production was positively related to DSE, in both ruderal hosts (native and exotic). We found remarkable relationships along a forest fragmentation gradient that reliably link forest fragment size to lower nutrient availability and increased mycorrhizal colonization in native/exotic ruderal hosts, while negatively linking AMF colonization to plant development and reproductive success.